Should doctors practise resuscitation skills on newly deceased patients? A survey of public opinion. - Tachakra, S (1998)
Trainee doctors must acquire skills in resuscitation, but opportunities for learning on real patients are limited. One option is to practise these skills in newly deceased patients. We sought opinions from 400 multiethnic guests at an open-access dinner dance for members of a local community. The questionnaire could elicit the responses strongly agree, agree, unsure, disagree or strongly disagree. 332 (83%) guests responded. For non-invasive techniques, 32% of responders supported practice without consent, 74% with consent. Support diminished with increasing invasiveness of procedure. 91% of the sample were uncomfortable about the procedures, the commonest reason being 'respect for the body' (264/302). 86% of responders felt that practice should last for no more than 5 minutes. The most popular solutions were for people to carry a personal card giving consent (89%) and establishment of a central register of individuals consenting to be practised upon after death (79%).